The study of using information and communication technology in Hungary and in the 27 countries of the EU - Peter Sasvari (International Journal of Advanced Research in Computer Science and Software Engineering, 2012)
The rate of personal computers and workstations in the 27 countries of the EU reached 96 %. The biggest backlog can be observed in the number of enterprises having and maintaining a website. Hungary's rate of 47 % is less than the EU average by 13 % and this rate was enough to overtake only two countries (Latvia and Portugal). In terms of small-sized enterprises having Internet access, Hungary, with 85 % came in last behind Lithuania (86 %) among the surveyed countries. The average penetration rate of intranet in the EU-25 was double than that of Hungary's.
Keywords: M13; M15; 330; Internet access; Local Area Network; Intranet; Proportion of using banking and financial services